Cláusula de não concorrência no contrato de trabalho: licitude e direitos fundamentais - Martinez Neto, Aldo Augusto (2012)
The overcoming of legal positivism, as well as recognition of the normative force of the Constitution of the Federative Republic of Brazil, led the incidence of human rights in private relations, among them labor relations with emphasis on employment agreement. As employees and employers are both holders of human rights, there are situations in which it checks for collision between the opposing fundamental rights. In order to solve the contradiction of human rights it is necessary to apply the principle of proportionality (adequacy, necessity and proportionality in the strict sense). We applied the principle of proportionality to reexamine the assumptions of non-compete clause to be effective after employment agreement termination in view of the collision between employees‟ human rights of freedom of work and employer's human rights of property. Applying the principle of proportionality it is possible to conclude that non-competition clause is in compliance with Brazilian labor legislation if the agreement observes the following assumptions: (i) justification for the restriction cause, (ii) temporal and geographical limitations, (iii) description of the activities and constraint of the object and (iv) financial compensation